Dilema Fiduciary Duty Theory dan Misappropriation Theory Dalam Kejahatan Pasar Modal di Indonesia - Syazali, Emir Adzan (Legalitas: Jurnal Hukum, 2023)
Crime in the capital market is a matter of great urgency for every investor in ensuring legal certainty involving in Indonesia many cases that have occurred in the capital market that have not reached court, this has many causal factors starting from company organs related to information in public offerings and OJK in this case as the supervisor of the capital market because of the problem of Implications of Fiduciary Duty Theory and Misappropriation Theory in capital market crimes in Indonesia. writing using normative juridical legal methods, namely library law research and the results of research on the Capital Market Law need to be revised to suit the times. By comparing the two theories above, and analyzing articles 95 and 97 UUPM which regulate legal subjects, it can be seen that Fiduciary duty has weaknesses and results in legal loopholes exacerbated by the rapid advancement of technology so that an outsider who accidentally obtains material information/facts is very likely to be free from insider trading in Indonesia.